Development of an Aza-Piancatelli-Templated Reaction Manifold from 4-Aminocyclopentenones: Access to Complex Carbocyclic Assemblies - Jagadeesh, Chenna; Mondal, Biplab; Saha, Jaideep (Synlett, 2022)
Capitalizing on the propensity of 1,2-amino group migration in γ-aminocyclopentenone with a suitable promoter, gem-diaryl-equipped systems unfolded an unprecedented avenue for the Lewis acid promoted displacement of γ-aniline group with nucleophiles such as indole. Such transformation, besides providing a means for direct γ-functionalization of cyclopentenones, presented innumerable scope for β,γ-annulation. Various tailored indolo bisnucleophiles were explored in the current study that rendered an array of indole alkaloid-like compounds in excellent yields and selectivity through one-pot operation. Analysis of collective experimental observation along with designed control experiments strongly suggested the possibility of a retro aza-Piancatelli rearrangement, which is hitherto unknown in the context. Such repertoire could find potential applications in the synthesis of complex assemblies from the Piancatelli rearrangement and related processes.1 Introduction2 Aza-Piancatelli Rearrangement and Related Domino Processes3 An Unprecedented Aza-Piancatelli-Templated Strategy for Polycyclic Assemblies4 Summary and Outlook
Keywords: Indoles; aza-Piancatelli rearrangement; annulation; bisnucleophiles; cyclopentenone